AKUPRESUR 3 TITIK TUBUH MENGURANGI NYERI HAID - Marlinda Marlinda; Nuria Muliani; Ayu Meidita Christiani; Yeti Septiasari (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2022)
Adolescents will experience physical and hormonal development as a sign of reproductive organ maturity which is marked by the appearance of menstruation. One of the problems experienced by adolescents with menstrual pain is menstruation. Management that can be done to treat desminorrhea pain is 3 acupressure points. The purpose of this study was to determine the effect of giving acupressure 3 points on the body pain of Menstruating Teenage Girls in the Working Area of ​​SMP N 1 Abung Selatan. The research design used was an analytical pre-experiment with a one group pretest-posttest approach and in this study did not use a control class or comparison group. The population in this study was teenage girls who had a history of dysmenorrhea at SMPN 1 Abung Selatan totaled 30 people, with the sample criteria still experiencing dysmenorrhea. The sampling technique used is total sampling. Analysis of the data used in this study is the Paired Test. The results of the univariate analysis revealed that the average respondent's pain score before the intervention was 4.03 and the average respondent's pain score after the intervention was 2.03. The results of the bivariate analysis revealed that there was an effect of giving 3 points of acupressure on the rate of reduction in menstrual pain in students of SMPN 1 Abung Selatan. with a p-value of 0.000. This research is expected to improve the quality reproductive health services especially for teenagers and the independent for teenage girls when experiencing resolving dysmenorrhea.